Cluster Analysis of Jakarta Islamic Index (JII) Stocks Based on Risk Adjusted Return - Pratama, Adrian Irnanda; Akbar, Rizky Aulya; Huang, Jyun Ping (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
This study is to examine the Jakarta Islamic Index (JII) stock clusters based on stock performance as measured using risk-adjusted returns for twenty-one semester periods 2009 - 2019. This study shows an alternative that can be utilized by investors supporting their decision to invest in the Indonesian Islamic finance industry. Data were collected through the online service feature of Yahoo! Finance and Google Finance total 43 companies with positive return. This study used quantitative analysis, Sharpe ratio was used to measure stock performance, K-mean clustering for cluster analysis and the Elbow method was used to determine the optimal number of clusters. The results showed that the 4 optimal number of clusters. Where cluster 1 determine the extreme return (5 companies), cluster 2 represent high return (12 companies), cluster 3 medium return (17 companies) and cluster 4 sufficient return (9 companies).